How does Information Exposure Affect Public Attitudes Toward GMO in China? The mediating and moderating roles of Conspiracy Belief and Knowledge - Du, Zhitao; Xiao, Yuqi; Xu, Jinghong (Frontiers in Psychology, 2022)
Background In China, controversy about genetically modified organisms (GMO) is ongoing and some regard GMO as a “product of a conspiracy,” which affects people’s attitudes (PAs) toward GMO. Beliefs in conspiracy theories (BCT) are formed from the information that people are exposed to. Information exposure not only constructs a pseudo-environment for individuals to perceive the world, but also generates external stimuli for their mental states and attitudes. People’s objective knowledge and self-assessed knowledge play an important moderating role in this process. Method The study adopted the stimulus-organism-response (SOR) model, with conspiracy beliefs as mediating variables, to test the mechanism of the independent variable of information exposure on the dependent variable of PAs toward GMO. Objective knowledge and self-assessed knowledge were introduced as moderator variables to explore the different roles of knowledge. A survey of Chinese adults was conducted in February 2022, and partial least squares structural equation modeling (PLS-SEM) was employed to estimate the multi-construct relationships. Results Information exposure was significantly and directly connected with PAs toward GMO. BCT also played a significant mediating role. Unofficial information exposure reinforced beliefs in conspiracy theories. Stronger beliefs in conspiracy theories reduced people’s willingness to consume GMO foods and made them pessimistic about the development prospects of GMO foods. In contrast, exposure to official information weakened people’s beliefs in conspiracy theories and increased their willingness to consume GMO foods. In addition, the level of knowledge had a moderating role. Individual’s objective knowledge can effectively reduce the negative relationship of conspiracy beliefs on attitudes toward GMO development. Conversely, individual’s self-assessed knowledge can enhance the negative relationship of conspiracy beliefs on attitudes toward GMO development. Conclusion Based on psychological and cognitive dimensions, this study provides a new perspective on how information exposure and people’s attitudes toward GMO are related to each other and enriches the variable measurement dimension of knowledge. Simultaneously, it provides a localized explanation of the factors affecting people’s attitudes toward GMO in China, providing a new theoretical basis for the subsequent development strategy of GMO foods.